The Association of Sprint Performance with Anthropometric Parameters in Youth Soccer Players - Arjan Hyka; Edmond Bicoku; Ali Mysliu; Agron Cuka (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2017)
Several studies have investigated the association between strength and speed, showing that stronger athletes perform better during sprint performances (Baker & Nance, 1999). Moreover, the aim of this study was to evaluate the correlation between sprint performance and anthropometric parameters. Subjects were 32 youth soccer players. The age of participants was 15.1±0.3 years. Speed time (50 m sprint) was evaluated during sprint test, and anthropometric parameters were measured (weight, height, percent body fat). Correlation analysis (Pearson test) was performed to evaluate the correlation between speed and anthropometrics. Results showed correlation between body weight and speed (r=-0.041 Sig=0.834); BMI values and speed (r=0.231; Sig=0.236), body height and speed (r=-0.384; Sig=0.044); percent body fat and speed (r=0.440; Sig=0.019).In conclusion, the results of this study show no significance association between body weight and BMI with sprint performance and significance correlation between body height (negative correlation) and percent body fat (positive correlation) with speed.